Prognostic and Therapeutic Roles of the Insulin Growth Factor System in Glioblastoma - Tirrò, Elena; Massimino, Michele; Romano, Chiara; Martorana, Federica; Pennisi, Maria Stella; Stella, Stefania; Pavone, Giuliana; Di Gregorio, Sandra; Puma, Adriana; Tomarchio, Cristina; Vitale, Silvia Rita; Manzella, Livia; et al. (Frontiers in Oncology, 2021)
Glioblastoma multiforme (GBM) is the most common primary brain malignancy and is often resistant to conventional treatments due to its extensive cellular heterogeneity. Thus, the overall survival of GBM patients remains extremely poor. Insulin-like growth factor (IGF) signaling entails a complex system that is a key regulator of cell transformation, growth and cell-cycle progression. Hence, its deregulation is frequently involved in the development of several cancers, including brain malignancies. In GBM, differential expression of several IGF system components and alterations of this signaling axis are linked to significantly worse prognosis and reduced responsiveness to temozolomide, the most commonly used pharmacological agent for the treatment of the disease. In the present review we summarize the biological role of the IGF system in the pathogenesis of GBM and comprehensively discuss its clinical significance and contribution to the development of resistance to standard chemotherapy and experimental treatments.